The impact of Allergan implant-related issues on patients with breast implants for reconstruction - Ji Min Kim; Woo Jin Song; Hyun Gyo Jeong; Sang Gue Kang (Archives of Aesthetic Plastic Surgery, 2021)
Background In August 2019, the Ministry of Food and Drug Safety and the Korean Society of Plastic and Reconstructive Surgeons confirmed the first case report of breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) in Korea and provided recommendations. This study was conducted to evaluate the impact of the first case report of BIA-ALCL on patients and whether the impact could be mitigated through expert recommendations. Methods A retrospective chart review was performed of patients who underwent implant-based breast reconstruction using Biocell textured breast implants at Soonchunhyang University Hospital. After the first case report of BIA-ALCL and informing the patients via text messages, the pattern of outpatient visits and the proportion and indications of outpatient office visitors who received reoperations were analyzed. Results After the first BIA-ALCL case report in Korea, 12 patients underwent reoperations due to other complications identified incidentally, while only three patients underwent prophylactic surgery. Among the patients who underwent reoperation after the Allergan issues, 76.7% received implant exchange. There was no significant difference in the proportion of reoperation types before and after the Allergan issues and the transmission of text messages (P=0.700). Conclusions Despite the major issues, outpatients were managed successfully according to our recommendations. The study found a low rate of regular outpatient visits; however, our efforts increased this rate. Therefore, methods for appropriate information delivery are needed for outpatient visits, as well as a system for regular monitoring. As experts, plastic surgeons should provide responsible leadership in this situation to relieve patients’ concerns.